From mouse to mermaid : the politics of film, gender, and culture - Bell, Elizabeth, 1953 November 1-; Haas, Lynda; Sells, Laura (Indiana University Press, 1995)
From Mouse to Mermaid, an interdisciplinary collection of original essays, is the first comprehensive, critical treatment of Disney cinema. Addressing children's classics as well as the Disney affiliates' more recent attempts to capture adult audiences, the contributors respond to the Disney film legacy from feminist, marxist, poststructuralist, and cultural studies perspectives. The volume contemplates Disney's duality as an American icon and as an industry of cultural production, created in and through fifty years of filmmaking. The contributors treat a range of topics at issue in contemporary cultural studies: the performance of gender, race, and class; the engendered images of science, nature, technology, family, and business. The compilation of voices in From Mouse to Mermaid creates a persuasive cultural critique of Disney's ideology. The contributors are Bryan Attebery, Elizabeth Bell, Claudia Card, Chris Cuomo, Ramona Fernandez, Henry A. Giroux, Robert Haas, Lynda Haas, Susan Jeffords, N. Soyini Madison, Susan Miller, Patrick Murphy, David Payne, Greg Rode, Laura Sells, and Jack Zipes.